A cluster-based approach against wormhole attacks in MANETs among smart grid - Liu, Weijie; Chen, Zhiran; Yu, Xiang; Zhou, Xue (Frontiers in Energy Research, 2022)
Mobile ad hoc networks in smart grid become more and more popular and significant. However, the deployment scenarios, the functionality requirements and the limited capabilities make them vulnerable to a large group of attacks, e.g., wormhole attacks. In this paper, a novel cluster-based scheme is proposed for the purpose of preventing wormhole attacks. Firstly, a clustering algorithm is proposed that employs a powerful analytical hierarchy process methodology to elect clusterheads. Afterwards, the elected clusterheads are required to implement the wormhole attacks prevention scheme which includes two phases, i.e., detection phase and location phase. By detection phase, the existence of wormhole attacks can be detected. By location phase, the wormhole nodes are able to be detected. Simulation results indicate the scheme in our paper can be used to prevent wormhole attacks in ad hoc networks efficiently.